1977
DOI: 10.1111/j.1151-2916.1977.tb15493.x
|View full text |Cite
|
Sign up to set email alerts
|

Tritium Diffusion in A12O3 and BeO

Abstract: Tritium diffusion in aluminum and beryllium oxides was studied by recoiling tritium into specimens and measuring the time rate of tritium release during postirradiation heating. Results were consistent with classical diffusion solutions and gave single values for the diffusion activation energy over the temperature range of measurement for single‐crystal, sintered, and powdered specimens. Varying amounts of tritium were released as tritiated water even after attempts to remove most of the water absorbed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 17 publications
10
60
0
Order By: Relevance
“…However, the effects of trapping are dearly evident because the breakthrough time in the absence of trapping would have been 0.0506 seconds for the same parameters otherwise. In Figure 5 note that the permeation turns on much more abruptly than in Figure 4, and it agrees quite well with the breakthrough time of 500 seconds calculated by Equation (11). There is some diffusive permeation before the theoretical breakthrough time and it takes a while Time (s) Figure 5.…”
Section: Effective-diffusivity Trapping In a Slabsupporting
confidence: 77%
“…However, the effects of trapping are dearly evident because the breakthrough time in the absence of trapping would have been 0.0506 seconds for the same parameters otherwise. In Figure 5 note that the permeation turns on much more abruptly than in Figure 4, and it agrees quite well with the breakthrough time of 500 seconds calculated by Equation (11). There is some diffusive permeation before the theoretical breakthrough time and it takes a while Time (s) Figure 5.…”
Section: Effective-diffusivity Trapping In a Slabsupporting
confidence: 77%
“…It is reported that the diffusion coefficient of hydrogen in the carbon steels ranges from 4:2 Â 10 À9 $1:0 Â 10 À8 m 2 /s, 14,18) while that in the Al 2 O 3 ranges from 3:4 Â 10 À46 $2:6 Â 10 À29 m 2 /s. 19) Thus, it is assumed that the low diffusivity of hydrogen in the Al 2 O 3 is closely related to the HMT result obtained in this study, in which silver particles were not visible directly on the Al 2 O 3 inclusions. Otsuka reported 20) on the basis of tritium autoradiography (TAR) that tritium was trapped on the interface between matrix phases and Al 2 O 3 inclusions in steel.…”
Section: Interaction Of Hydrogen With Inclusionssupporting
confidence: 75%
“…Thus, we can conclude that the composition and the crystal structure of the oxide scale are even, and the difference between the two layers is just their compactness. At high temperature, H 2 O tends to dissociate at the defects on TiO 2 /(110) planes into free H atoms and OH groups [21][22][23]. The generated hydrogen atoms are more prone to diffuse into TiO 2 through the crystal channels in the c-axis direction, along which the diffusion rate is at least one order of magnitude larger than that in the direction perpendicular to c-axis [21,22].…”
Section: Corrosion Behavior Of Pure Ti Under a Solid Depositmentioning
confidence: 99%
“…At high temperature, H 2 O tends to dissociate at the defects on TiO 2 /(110) planes into free H atoms and OH groups [21][22][23]. The generated hydrogen atoms are more prone to diffuse into TiO 2 through the crystal channels in the c-axis direction, along which the diffusion rate is at least one order of magnitude larger than that in the direction perpendicular to c-axis [21,22]. This dissolution of hydrogen in TiO 2 can increase the concentration of crystal defects by forming hydrogen defects, thereby increasing the diffusion outward of Ti ions [23].…”
Section: Corrosion Behavior Of Pure Ti Under a Solid Depositmentioning
confidence: 99%